2022
DOI: 10.3389/fpsyg.2022.994209
|View full text |Cite
|
Sign up to set email alerts
|

Research on the influence of college students’ participation in sports activities on their sense of inferiority based on self-esteem and general self-efficacy

Abstract: College students need to face various problems and conflicts, and are prone to many negative emotions, such as depression, low self-esteem, social anxiety, low sense of belonging, lack of self-identity, and so on. The generation of these bad emotions will bring unexpected negative effects to college students. Taking Chinese college students as the research object, this study analyzes the influence of sports participation on inferiority. Furthermore, we explored whether self-esteem and general self-efficacy med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…These two effects are now considered the most established findings in the SE literature (Trzesniewski et al, 2013;Orth and Robins, 2014). These studies also suggest that gender differences are determined, at least in part, by universal mechanisms that reflect both universal sociocultural factors and genetic biological processes that transcend culture and context (Gao et al, 2020;Liu, 2022). Moderate global SE, which was slightly higher than that in our study [2.997 (0.516) vs. 3.14 (0.56)], was also reported in 292 Saudi people with disabilities, with a clear male superiority over females.…”
Section: Discussionmentioning
confidence: 93%
“…These two effects are now considered the most established findings in the SE literature (Trzesniewski et al, 2013;Orth and Robins, 2014). These studies also suggest that gender differences are determined, at least in part, by universal mechanisms that reflect both universal sociocultural factors and genetic biological processes that transcend culture and context (Gao et al, 2020;Liu, 2022). Moderate global SE, which was slightly higher than that in our study [2.997 (0.516) vs. 3.14 (0.56)], was also reported in 292 Saudi people with disabilities, with a clear male superiority over females.…”
Section: Discussionmentioning
confidence: 93%
“…This sense of inferiority could subsequently trigger or exacerbate depressive symptoms. Inferiority could potentially lead to negative self-esteem and lack of self-worth, key aspects often associated with depressive states (59)(60)(61)(62)(63)(64). On the other hand, "gloomy feelings" serving as a bridge node indicates that these symptoms are not only a consequence of internalized HIV stigma, but could also potentially feed back into the internalized HIV stigma cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy serves as a crucial intermediary factor between an individual’s subjective exercise experience and the development of anxiety disorder. Several studies have demonstrated that the subjective exercise experience can alleviate anxiety by enhancing an individual’s self-efficacy ( Liu, 2022 ; Wang et al, 2022 ). This study used the subjective exercise experience, self-efficacy, and Generalized Anxiety Disorder scales to investigate 300 University students.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%